Hubungan Partisipasi Petani dengan Keberlanjutan Sistem Pertanian Terpadu Mina Padi - Esti Ittaqillah; Dwi Sadono; Endang Sri Wahyuni (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2020)
The government is currently developing an integrated agricultural system for mina padi in order to optimize agricultural land that can increase the productivity of agricultural land, improve the welfare of farmers and support food security. Farmers participation in implementing the mina padi system is expected to support sustainable agriculture in the ecological, economic, social, technology-infrastructure and institutional dimensions. This study aims to analyze the relationship between the level of farmer participation and the sustainability of the integrated mina padi farming system. Data were collected using a questionnaire instrument and analyzed using the Rank Spearman correlation test. The results of the study involving 42 respondents showed that farmers were considered to be quite participatory and the rice mina system was quite sustainable. Farmer characteristic that significantly related to the level of participation is the level of cosmopolitan. The external factors that significantly related to the level of participation, are the role of instructors, market access, and information availability. The level of participation, in general, is significantly related to all dimensions the level of sustainability, including ecological, economic, social, infrastructure-technology, and institutional dimensions.Keywords: sustainability, mina padi, participation, integrated farming. ABSTRAKPemerintah saat ini sedang mengembangkan sistem pertanian terpadu mina padi dalam rangka mengoptimalisasi lahan pertanian yang dapat meningkatkan produktivitas lahan pertanian, menyejahterakan petani dan mendukung ketahanan pangan. Partisipasi petani dalam menerapkan sistem mina padi diharapkan dapat mendukung pertanian berkelanjutan pada dimensi ekologi, ekonomi, sosial, teknologi-infrastruktur dan kelembagaan. Penelitian ini bertujuan menganalisis hubungan antara tingkat partisipasi petani dengan keberlanjutan sistem pertanian terpadu mina padi. Data dikumpulkan menggunakan instrumen kuesioner dan dianalisis menggunakan uji korelasi Rank Spearman. Hasil penelitian yang melibatkan 42 responden menunjukkan bahwa petani tergolong cukup partisipatif dan sistem mina padi yang cukup berkelanjutan. Karakteristik petani yang berhubungan nyata dengan tingkat partisipasi yaitu tingkat kekosmopolitan. Faktor eksternal yang berhubungan nyata dengan tingkat partisipasi yaitu, peran penyuluh, tingkat akses pasar, dan ketersediaan informasi. Tingkat partisipasi secara umum berhubungan nyata dengan semua dimensi tingkat keberlanjutan, yaitu dimensi ekologi, ekonomi, sosial, teknologi-infrastruktur dan kelembagaan.Kata kunci: keberlanjutan, mina padi, partisipasi, pertanian terpadu.